Sistem Pendukung Keputusan Evaluasi Kepuasan Reseller Di Toko Callista Bandungan Dengan Metode Simple Additive Weighting (Saw) - Munawaroh, Lutfi; Sipayung, Yoannes Romando (Jurnal Tika, 2023)
Along with the development of the times and increasingly sophisticated technology in the modern era. Callista wholesale warehouse store in the largest and most complete wholesale werehouse located on Jalan Raya Bandungan – Ambarawa, Bandungan Dostrict Semarang, Regency, Based on the problems that were in the Callista store regarding customer satisfaction, it was still used manually for reports and filling out questionnaires. With the manual method, of course, it creates a lot of difficulties for the owner in processing data and making satisfactionreports. Given these problems a sistem  will be created to help reseller get good service from Callista store, namely in the form of a satisfactionsistem  that user the web indicated for Callista stores.